Histomorphometrical and molecular evaluation of endosseous dental implants sites in humans: Correlation with clinical and radiographic aspects - Pereira, Andrea Castro; Souza, Pedro Paulo Chaves [UNESP]; Souza, João Antonio Chaves [UNESP]; Silva, Tarcília Aparecida; Batista, Aline Carvalho; Ribeiro-Rotta, Rejane Faria (Wiley, 2013)
Objective: To evaluate the correlations between clinical-radiographical aspects and histomorphometric-molecular parameters of endosseous dental implant sites in humans. Material and methods: The study sample consisted of bone implant sites from the jawbones of 32 volunteers, which were classified according to two different systems: (1) based only on periapical and panoramic images (PP); (2) as proposed by Lekholm & Zarb (L&Z). Bone biopsies were removed using trephine during the first drilling for implant placement. Samples were stained with haematoxylin-eosin (HE), and histomorphometric analysis was performed to obtain the following parameters: trabecular thickness (Tb.Th), trabecular number, bone volume density (BV/TV), bone specific surface (BS/BV), bone surface density and trabecular separation (Tb.Sp). In addition, immunohistochemistry analysis was performed on bone tissue samples for the proteins, Receptor activator of nuclear factor kappa-B (RANK), RANK ligand (RANKL), osteoprotegerin (OPG) and Osteocalcin (OC). Also, the determination of the relative levels of gene expression was performed using Reverse transcription-real-time Polymerase Chain Reaction (RT-PCR). Results: PP and L&Z classification systems revealed a moderate correlation with BV/TV, BS/BV, Tb.Th and Tb.Sp. L&Z's system identified differences among bone types when BV/TV, BS/BV, Tb.Th and Tb.Sp were compared. A weak correlation between PP/L&Z classifications and the expression of bone metabolism regulators (RANK, RANKL, OPG e OC) was found. The analysis of mRNA expression showed no difference between the bone types evaluated. Conclusions: Our results suggest that PP and L&Z subjective bone-type classification systems are related to histomorphometric aspects. These data may contribute to the validation of these classifications. Bone remodelling regulatory molecules do not seem to influence morphological aspects of the jawbone © 2011 John Wiley & Sons A/S.
Keywords: Bone density; Dental implants; Histomorphometry; Immunohistochemistry